Hadith Preservation: Techniques And Contemporary Efforts - Haruna Babatunde Jaiyeoba; Noor Mohammad Osmani (Universiti Sains Islam Malaysia, 2024)
Journal of Fatwa Management and Research, Volume 29 Issue 3 Page (31–45)